Die telos van die unieke tipering van die wederkoms as die parousia van die Seun van die Mens - van Rhyn, H.P. Malan (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2026)
The telos of the unique designation of the Second Coming as the parousia of the Son of Man in Matthew 24. This article investigates the unique and purposeful characterisation of the Second Coming of Jesus Christ as ἡ παρουσία τοῦ υἱοῦ τοῦ ἀνθρώπου [the parousia of the Son of Man] as found exclusively in Matthew 24. This phrase, appearing only three times in the New Testament, all within the same chapter, is exegetically and theologically loaded. Using a grammatical-historical and revelation-historical methodology, this study explores the telos [purpose] of this specific revelation within its eschatological context. The study begins with an exegetical analysis of the phrases ὁ υἱὸς τοῦ ἀνθρώπου [Son of Man] and παρουσία [parousia or coming]. The Son of Man, rooted in Daniel 7, is portrayed as a divine, ruling figure, not merely human. The title emphasises Christ’s divinity, kingship, mediatorship, and eternal reign. The term παρουσία, used technically in early Christianity to describe Christ’s eschatological return, signifies his visible, bodily, and glorious presence at the end of time as Judge and King. By combining these two theological concepts into one phrase, Matthew 24 creates what is rhetorically a pleonasm, yet theologically an intensification: a deliberate emphasis on the identity and majesty of Christ in his return. The context of Matthew 24 clarifies the goal of this revelation: to warn the disciples against deception, encourage their perseverance, and comfort them with the certainty of Christ’s return and deliverance. Contribution: The primary contribution of this study lies in identifying and analysing a theologically dense phrase that has been largely overlooked in scholarly literature. By formulating a comprehensive semantic definition of παρουσία and connecting it to the title the Son of Man, the article offers a new lens for interpreting Matthew 24. This phrase functions not merely as a descriptive term for Christ’s return but as a concentrated theological proclamation of who he is, how he will return, and what the glorious outcome of that return will be. Furthermore, the study demonstrates that this phrase serves multiple revelatory purposes [teloi]: polemical (against deception), pastoral (encouraging the faithful), ethical (calling for readiness and stewardship), and evangelistic (a call to repentance). The church is thus called to hopeful endurance in the face of suffering, armed with the assurance that the Son of Man will come visibly, gloriously, and triumphantly.